The G Protein-Coupled Receptor UT of the Neuropeptide Urotensin II Displays Structural and Functional Chemokine Features - Castel, Hélène; Desrues, Laurence; Joubert, Jane-Eileen; Tonon, Marie-Christine; Prézeau, Laurent; Chabbert, Marie; Morin, Fabrice; Gandolfo, Pierrick (Frontiers in Endocrinology, 2017)
The urotensinergic system was previously considered as being linked to numerous physiopathological states including atherosclerosis, heart failure, hypertension, pre-eclampsia, diabetes, renal disease, as well as brain vascular lesions. Thus, it turns out that the actions of the urotensin II (UII)/G protein-coupled receptor (GPCR) UT system in animal models are currently not predictive enough in regards to their effects in human clinical trials, and that urotensin II analogs established to target UT, were not as beneficial as expected in pathological situations. Thus many questions remain regarding the overall signaling profiles of UT leading to complex involvement in cardiovascular and inflammatory responses as well as cancer. We address the potential UT chemotactic structural and functional definition under an evolutionary angle, by the existence of a common conserved structural feature among chemokine, opioïdergic receptors and UT, i.e. a specific proline position in the transmembrane domain-2 TM2 (P2.58) likely responsible for a kink helical structure that would play a key role in chemokine functions. Even if the last decade was devoted to the elucidation of the cardiovascular control by the urotensinergic system, we also attempt here to discuss the role of UII on inflammation and migration likely providing a peptide chemokine status for UII. Indeed, our recent work established that UT activation by a gradient concentration of UII recruits Gαi/o and Gα13 couplings in a spatiotemporal way, controlling key signaling events leading to chemotaxis. We think that this new vision of the urotensinergic system should consider UT as a chemotactic therapeutic target in pathological situations involving cell chemoattraction.